Exploring Factors Affecting Health Care Providers' Behaviors for Maintaining Continuity of Care in Kerala, India; A Qualitative Analysis Using the Theoretical Domains Framework - Joseph, Linju; Greenfield, Sheila; Lavis, Anna; Lekha, T. R.; Panniyammakal, Jeemon; Manaseki-Holland, Semira (Frontiers in Public Health, 2022)
Introduction Access to patients' documented medical information is necessary for building the informational continuity across different healthcare providers (HCP), particularly for patients with non-communicable diseases (NCD). Patient-held health records (PHR) such as NCD notebooks have important documented medical information, which can contribute to informational continuity in the outpatient settings for patients with diabetes and hypertension in Kerala. We aimed to use the theoretical domains framework (TDF) to identify the perceived HCP factors influencing informational and management continuity for patients with diabetes and hypertension. Methods We re-analyzed semi-structured interview data for 17 HCPs with experience in the NCD programme in public health facilities in Kerala from a previous study, using the TDF. The previous study explored patients, carers and HCPs experiences using PHRs such as NCD notebooks in the management of diabetes and hypertension. Interview transcripts were deductively coded based on a coding framework based on the 14 domains of TDF. Specific beliefs were generated from the data grouped into the domains. Results Data were coded into the 14 domains of TDF and generated 33 specific beliefs regarding maintaining informational and management continuity of care. Seven domains were judged to be acting as facilitators for recording in PHRs and maintaining continuity. The two domains “memory, attention and decision process” and “environmental context and resources” depicted the barriers identified by HCPs for informational continuity of care. Conclusion In this exploration of recording and communicating patients' medical information in PHRs for patients with diabetes and hypertension, HCPs attributions of sub-optimal recording were used to identify domains that may be targeted for further development of supporting intervention. Overall, nine domains were likely to impact the barriers and facilitators for HCPs in recording in PHRs and communicating; subsequently maintaining informational and management continuity of care. This study showed that many underlying beliefs regarding informational continuity of care were based on HCPs' experiences with patient behaviors. Further research is needed for developing the content and appropriate support interventions for using PHRs to maintain informational continuity.